Research on chromium removal in water by modified bentonite - Son, Tran Van; Quy, Tran Van (VNU Journal of Science: Earth and Environmental Sciences; Vol 28 No 1, 2012)
Abstract . This research was conducted to produce a new natural derivated material (bentonite), which can remove chromium from aquatic environment. Natural bentonite was activated by HCl acid, then by thermal factor at 110 0 C. Results of SEM images show that spongy and surface area of modified bentonite larger than natural bentonite. Chromium adsorption ability on modified bentonite depends on pH of solution, and adsorption capacity is almost stable in the pH range from 3 to 6, then dramatically reduced from pH 6-11. Maximum chromium adsorption capacity of modified bentonite - B90at-2 (13,89 mgCr/g) was much more than natural bentonite - B90 (3,32 mgCr/g). The modified bentonite can be used for waste water treatment with high concentration of chromium (140 mg/L) meet the vietnamese standard (QCVN 24:2009/BTNMT, B column).    Keywords :  Modified Bentonite, montmorillonit, chromium, acid, adsorption.